Study of Chicory Utilization as Animal Feed: Analysis of Potential and Implementation Challenges in the Tropics - Amalyadi, Rezki; Widiastuti, Lusia Komala; Aminurrahman; Karni, Ine; Septian, I Gede Nano; Gifari, Zaid Al; Anwar, Khairil (Universitas Madako Tolitoli, 2026)
Cichorium intybus L. (chicory) is a perennial forage with considerable potential to support sustainable livestock systems, particularly in tropical regions. This study aims to evaluate its nutritional composition, agronomic performance, and livestock response. A literature-based review supported by field trial data was employed, focusing on nutrient analysis, cultivation practices, animal feeding performance, and economic viability. Quantitative findings indicate that chicory contains 14–22% crude protein and 10–20% inulin (dry weight basis), with forage yields reaching 8–12 t DM/ha/year under optimal management. Feeding trials demonstrate improvements in milk yield by 5–12%, reductions in nitrogen excretion by 10–15%, and decreases in gastrointestinal parasite load by 30–40% compared with conventional grass-based diets. Agronomically, chicory thrives in well-drained soils with balanced fertilization and responds positively to high-frequency irrigation and integrated pest management, although breeding for tropical adaptation remains essential. Despite its high nutritive value and bioactive properties, economic challenges such as high input costs and limited market access constrain broader adoption. Overall, chicory represents a promising alternative forage crop that enhances animal productivity, health, and environmental efficiency, while contributing to climate-resilient livestock production systems in tropical settings.